Myth, Dream, and Resistance in Ninotchka Rosca and Emmanuel Lacaba’s Fictions - Ojano, Kathrine Domingo (Animo Repository, 2022)
Despite Ninotchka Rosca’s international acclaim as a Feminist novelist and Emmanuel Lacaba’s national renown as a martyred resistance poet, the dearth of scholarship on their collections of short stories—written from around the time of the 1970 First Quarter Storm to the early years of Martial Law—has also left unanswered how their fictions evinced a new paradigm of resistance literature as the critique and revision of modernity in the Third World. In this paper, I address this gap by looking into Rosca’s transformation of fiction into mythopoeic speculations in The Monsoon Collection (1983) and Lacaba’s experimentation with oneiric or dream-like narratives in Salvaged Prose (1992). I argue that the fictions of these authors register the periphery and juncture of world modernity as the incomplete, delayed, or aborted self- and collective emergence of Filipinos. At the same time, the authors also revealed the normative relevance of resistance literature within and despite modernity, which is its capacity to rethink humanity as social and collective relations of social justice. Drawing on the volatile yet explosive zeitgeist of 1970s Manila, the authors therefore reconceived resistance writing from outside political orthodoxy into new artistic forms.